Optimization and characterization of biodegradable film based on glutinous flour/glycerol/chitosan/ZnO using Response Surface Methodology (RSM) - Central Composite Design (CCD) - Aulia Beta Safira; Aprilina Purbasari (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Starch-based films are considered more competitive than petroleum because they are renewable, environmentally friendly, and easily degraded. The film in this study was fabricated from white glutinous flour, glycerol, chitosan, and ZnO through a starch gelatinization process. Chitosan content ranges from 2-4% (w/v), ZnO 4-8% of the dry weight of solid, and glycerol 15-45% of the dry weight of solids with a mass of white glutinous flour as much as 3 g was determined. Optimization and determination of running variables based on Central Composite Design. Response variables such as tensile strength, elongation, and water absorption were observed as important parameters in applying film as packaging materials. The Design Expert program recommended 2 g of chitosan: 8 % ZnO: 36.02% glycerol as the best composition in film fabrication, which aims to obtain maximum tensile strength and elongation, as well as minimum water absorption with the maximum desirability value (0.660). The predicted response values under optimal conditions by RSM were 3.68 MPa for tensile strength, 86.79% for elongation, and 268.09% for water absorption. The actual response has a tensile strength of 3.31 MPa, elongation of 83.5%, and water absorption of 320%. On average, a white glutinous flour/glycerol/chitosan/ZnO-based film required ± 45 days to degrade in the soil completely.